Photosynthesis and carbon allocation are both important predictors of genotype productivity responses to elevated CO2 in Eucalyptus camaldulensis. (8th May 2018) - Aspinwall, Michael J; Blackman, Chris J; de Dios, Víctor Resco; Busch, Florian A; Rymer, Paul D; Loik, Michael E; Drake, John E; Pfautsch, Sebastian; Smith, Renee A; Tjoelker, Mark G; Tissue, David T
Abstract: Intraspecific variation in biomass production responses to elevated atmospheric carbon dioxide (eCO2 ) could influence tree species' ecological and evolutionary responses to climate change. However, the physiological mechanisms underlying genotypic variation in responsiveness to eCO2 remain poorly understood. In this study, we grew 17 Eucalyptus camaldulensis Dehnh. subsp. camaldulensis genotypes (representing provenances from four different climates) under ambient atmospheric CO2 and eCO2 . We tested whether genotype leaf-scale photosynthetic and whole-tree carbon (C) allocation responses to eCO2 were predictive of genotype biomass production responses to eCO2 . Averaged across genotypes, growth at eCO2 increased in situ leaf net photosynthesis ( A net ) (29%) and leaf starch concentrations (37%). Growth at eCO2 reduced the maximum carboxylation capacity of Rubisco (−4%) and leaf nitrogen per unit area ( N area, −6%), but N area calculated on a total non-structural carbohydrate-free basis was similar between treatments. Growth at eCO2 also increased biomass production and altered C allocation by reducing leaf area ratio (−11%) and stem mass fraction (SMF, −9%), and increasing leaf mass area (18%) and leaf mass fraction (5%). Overall, we found few significant CO2 × provenance or CO2 × genotype (within provenance) interactions. However, genotypes that showed the largest increases in total dry mass at eCO2 had larger increases in root mass fraction (with larger decreases in SMF) and photosynthetic nitrogen-use efficiency (PNUE) with CO2 enrichment. These results indicate that genetic differences in PNUE and carbon sink utilization (in roots) are both important predictors of tree productivity responsiveness to eCO2 .